SZ_GERICHTE BEK 2018 151 vom 13. Februar 2019 , Anordnung und Auftrag zur DNA-Profilerstellung - SZ Gerichte (2019)
Anordnung und Auftrag zur DNA-Profilerstellung | Zwangsmassnahmen/übrige Zwangsmassnahmen